Wider pelvic transverse and intertuberum diameter are risk factors for pelvic organ prolapse - Kadek Fajar Marta; Ketut Suwiyoga; I Wayan Megadhana (Indoscholar, 2020)
Background: Pelvic floor’s shape and size are suspected of having associations with the occurrence of pelvic organ prolapse (POP). However, these relationships are not definitive and have never been evaluated. This study aims to identify the relationship between POP and pelvic floor size. Methods: This is a cross-sectional study involving women with or without POP who underwent gynecologic visits at the outpatient clinic. POP was diagnosed using the POP-Q questionnaire, whereas pelvic floor diameter was measured from the x-ray, comprising anteroposterior (AP), transverse (TS), interspinous (IS), and intertuberous (IT) diameters. Results: The TS and IT diameter of subjects with POP are significantly wider (p<0.001 and p=0.016), on the other hand, the AP and IS diameter were similar among two groups (p=0.36 and p=0.58). The subjects who have TS and IT diameter each above 12.185 and 10.140 cm have a higher risk of POP when compared to those who have TS and IT diameter lesser than the corresponding values (PRTS 3.85, 95% CI1.47-20.11; p<0.001; PRIT 2.49, 95% CI 1.12-5.53; p=0.013), with both, have partial correlation but TS more significant (Lambda 0.7; p-value 0.001 and Lambda 0.4; p-value 0.075). There was a relationship between a pelvic floor with POP. Subjects with POP have wider TS and IT diameters when compared to non-POP subjects. Conclusion: TS and IT diameters above 12.185 cm and 10.140 cm increase the risk of POP.